2016
DOI: 10.1128/jvi.01362-16
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Metapneumovirus Binding to Heparan Sulfate Blocks Infection in Human Lung Cells and Airway Tissues

Abstract: Human metapneumovirus (HMPV), a recently discovered paramyxovirus, infects nearly 100% of the world population and causes severe respiratory disease in infants, the elderly, and immunocompromised patients. We previously showed that HMPV binds heparan sulfate proteoglycans (HSPGs) and that HMPV binding requires only the viral fusion (F) protein. To characterize the features of this interaction critical for HMPV binding and the role of this interaction in infection in relevant models, we utilized sulfated polysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 74 publications
0
57
1
Order By: Relevance
“…While some previous reports suggest inhibition of early stages of viral replication by carrageenans [19], we were not able to replicate these results. It is, however, possible that the mechanism of action may very depending on the origin of these natural polymers [15,20,21,26].…”
Section: Nspahs and Carrageenans Hamper Release Of Progeny Virions Frcontrasting
confidence: 97%
See 1 more Smart Citation
“…While some previous reports suggest inhibition of early stages of viral replication by carrageenans [19], we were not able to replicate these results. It is, however, possible that the mechanism of action may very depending on the origin of these natural polymers [15,20,21,26].…”
Section: Nspahs and Carrageenans Hamper Release Of Progeny Virions Frcontrasting
confidence: 97%
“…hMPV F protein utilizes heparan sulfate (HS), a negatively charged glycosaminoglycan (GAG) present on the cellular membrane, as an attachment factor [11]. Previous studies have shown that natural polysaccharides containing sulfonate groups efficiently inhibit infections caused by viruses employing HS during cell entry [12][13][14][15][16][17][18][19] and it was proposed that carrageenans inhibit the attachment of the hMPV to HS by interacting with the F protein [19]. It is, however, worth to mention that replication of some HS independent viruses is also hampered in the presence of these polymers [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These results reinforce the conclusion that ESCd are significantly more susceptible to ZIKV U than to ZIKV C . Discussion ZIKV entry into target cells is a complex, multistep process and has implicated several host molecules, including the TAM receptors, HAVCR1 (the hepatitis C receptor, sometimes known as TIM1 or TIMD1), CD209 (DC-SIGN1), attendant linker proteins PROS1 and GAS6 that associate with phosphatidylserine on the capsid surface, and proteoglycans, especially heparan sulfates that appear to form the primary attachment sites for many kinds of viruses (45)(46)(47)(48), including DENV2 (49). Villous trophoblast cells obtained from term placentas, which are resistant to a wide range of viruses (23), including ZIKV (24), appear to lack most, if not all, these candidate attachment factors ( Fig.…”
Section: Release Of Infection-competent Virus By Esc and Esc-derived mentioning
confidence: 99%
“…The antiviral effect relies on the binding mechanism of the nanoparticles to the virus surface, thus preventing virus-cell attachment. In most cases, the reversibility of these bonds is reported [169], so that by increasing the dilution viral inhibition is lost, causing those compounds not to be considered antiviral drugs. The aforementioned authors have designed antiviral nanoparticles of virucidal effect based on long and flexible linkers simulating HSPG, leading to irreversible viral deformation.…”
Section: Broad-spectrum Antiviral Npsmentioning
confidence: 99%